Views of the Elderly Regarding the Behavior by His Family Members - Siddique, Abu Bakar (Medicine Today, 2015)
This was a Cross-sectional Study conducted in urban area of Dhaka city corporation, During the Period of 1st January to 30th June 2009, with a view to assessing the views of elderly regarding the behavior by his family members. A total of 150 respondents of both sexes 60 years and above were interviewed of which 60% were males and 40% were female, 57.33% were in the age group of 60-69 years. 10% were illiterate 90% were from literate group. Among the respondents 90.66% were Muslim, 34% were retired, 46% came from joint family, most of the respondents family income above 10000 thousand taka per month, 58% of the respondents were neglected by family members, 71.33% of the respondents were not get properly take care from family members, and 66% were unhealthy. Among the major health problems 10.66% had diseases of bones & Connective tissue, 9.33% general weakness, 8% GIT problems, 6.67 % had cardiovascular diseases, 4.67% had respiratory diseases. and 3.33% had diabetic, The study shows that the respondents were deprive from take care of their family members due to some factors, which include family members have no time (76%),they are busy (80.67%), no earning capacity (56.67%), The study revealed that 64% of the respondents were not respected, 34% were not take part in familial decision making, 44.67% were never seeking advice by family members, 61.33% some times take part in familial program and elderly experience were not respected 69.33%.In this study we found that 80.66% of the respondents feel lonely, 73.33% of the elderly not satisfied according to current behaved and Almost 100% respondents want soft and polite behaved and shelter during old age and want all kinds of support requiring elderly life leading. The findings of the present study showed that the elderly people were unhappy and not satisfy to take care of their family members, their loneliness and misery is indescribable and suffering from different health & mental problems. It is considered that the findings of the study will not only help as guideline for some preventive program, but also serve as useful basis for future step, research and planning. Medicine Today 2014 Vol.26(2): 104-110